Opium regimes : China, Britain, and Japan, 1839-1952 - Brook, Timothy, 1951-; Wakabayashi, Bob Tadashi, 1950- (Berkeley : University of California Press, 2000)
Opium Regimes draws on a range of research to show that the opium trade was not purely a British operation, but involved Chinese merchants and state agents, and Japanese imperial agents as well.
Introduction : Opium's history in China / Timothy Brook and Bob Tadashi Wakabayashi -- Opium for China : the British connection / Gregory Blue -- From peril to profit : opium in late-Edo to Meiji eyes / Bob Tadashi Wakabayashi -- Drugs, taxes, and Chinese capitalism in Southeast Asia / Carl A. Trocki -- The Hong Kong opium revenue, 1845-1885 / Christopher Munn -- Opium in Xinjiang and beyond / David Bello -- Drug operations by resident Japanese in Tianjin / Motohiro Kobayashi -- Opium/leisure/Shanghai : urban economies of consumption / Alexander Des Forges -- Opium and modern Chinese state-making / R. Bin Wong -- Opium and the state in late-Qing Sichuan / Judith Wyman -- Poppies, patriotism, and the public sphere : nationalism and state leadership in the anti-opium crusade in Fujian, 1906-1916 / Joyce A. Madancy -- The National Anti-Opium Association and the Guomindang state, 1924-1937 / Edward R. Slack Jr. -- Opium control versus opium suppression : the origins of the 1935 six-year plan to eliminate opium and drugs / Alan Baumler -- The responses of opium growers to eradication campaigns and the poppy tax, 1907-1949 / Lucien Bianco -- Opium and collaboration in Central China, 1938-1940 / Timothy Brook -- An opium tug-of-war : Japan versus the Wang Jingwei regime / Motohiro Kobayashi -- Resistance to opium as a social evil in wartime China / Mark S. Eykholt -- Nationalism, identity, and state-building : the antidrug crusade in the People's Republic, 1949-1952 / Zhou Yongming.
Includes bibliographical references (pages 405-429) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Opium trade -- China -- History; Drug traffic -- China -- History; Drug control -- China -- History; China -- Relations -- Great Britain; Great Britain -- Relations -- China; China -- Relations -- Japan; Japan -- Relations -- China; Opium -- Commerce -- Chine -- Histoire; Drogues -- Trafic -- Chine -- Histoire; Lutte antidrogue -- Chine -- Histoire; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; Drug control; Drug traffic; Opium trade; International relations; China; Great Britain; Japan; History